1967
DOI: 10.1017/s0021859600017913
|View full text |Cite
|
Sign up to set email alerts
|

A study of the composition of Clun Forest ewe's milk:III. Ewe's milk fat: a preliminary study

Abstract: 1. Milk fat obtained from six Clun Forest ewes was analysed in the 1st, 4th, 8th and 12th weeks of lactation for fat constant values and fatty-acid composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The ewes and lambs grazed knowledge, been published. permanent pasture during the spring of 1968, and In previous papers, Ashton et al (1964), Ashton were fed a small amount of a commercial ewe-and-& Yousef (1966) and Yousef & Ashton (1967) lamb concentrate daily up to 6 weeks after parturireported the gross composition of milk constituents, tion. One of the ewes died 6 weeks after lambing, the mineral composition and a preliminary study and the experiment was continued with the of the milk fat of Clun Forest ewes.…”
Section: Introductionmentioning
confidence: 99%
“…The ewes and lambs grazed knowledge, been published. permanent pasture during the spring of 1968, and In previous papers, Ashton et al (1964), Ashton were fed a small amount of a commercial ewe-and-& Yousef (1966) and Yousef & Ashton (1967) lamb concentrate daily up to 6 weeks after parturireported the gross composition of milk constituents, tion. One of the ewes died 6 weeks after lambing, the mineral composition and a preliminary study and the experiment was continued with the of the milk fat of Clun Forest ewes.…”
Section: Introductionmentioning
confidence: 99%
“…TMTTJ nTvrTr"rTrwr ^n e ^r s * a m l °^ tn^s investigation was to compare the milk yield ol a group of ewes obtained by a Previous papers in this series (Ashton, Owen & lamb-suckling technique with that obtained by Ingleton, 1964;Ashton & Yousef, 1966; Yousef & machine milking following oxytocin injection. The Ashton, 1967;Poulton & Ashton, 1970) have dealt second aim was to study the effect of a cereal-rich mainly with the compositional aspects of ewe's diet, as opposed to the more normal diet of hay milk without reference to yield of milk or milk and commercial concentrates, on the yield of milk constituents. Information on the milk yield of ewes and its constituents.…”
mentioning
confidence: 99%
“…Such information may have potential application for both animal breeders and those who use animals for certain nutritional or related studies. An illustration of this is the recent report by Yousef & Ashton (1967) in which they indicated that differences existed among individual ewes for percentage fatty acid composition of milk fat and they also suggested that breed differences might exist. The mice used in this study provided evidence that genetic differences existed between inbred lines for certain carcass traits including relative amounts of fatty acids.…”
Section: Discussionmentioning
confidence: 99%